2014
DOI: 10.1002/lt.23912
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of donor follow-up after living donor liver transplantation

Abstract: Donor safety in living liver donation is of paramount importance, however, information on long-term outcomes is limited by incomplete follow-up. We sought to ascertain factors that predict post-donation follow-up in 456 living liver donors in the Adult-to-Adult Living Donor Liver Transplantation Cohort Study (A2ALL). Completed donor follow-up was defined as physical, phone, or laboratory contact at a given time point. Univariate and multivariable mixed effects logistic regression models were developed to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…For example, few A2ALL donors had follow-up >6 years (24); it is unknown whether additional complications may develop later. In addition, after the first year or so postdonation, many donors may have sought care at facilities other than the transplant center.…”
Section: Long-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, few A2ALL donors had follow-up >6 years (24); it is unknown whether additional complications may develop later. In addition, after the first year or so postdonation, many donors may have sought care at facilities other than the transplant center.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…In the United States, the Scientific Registry of Transplant Recipients is conducting a feasibility study to explore whether a living kidney and liver donor registry could be formed to collect long-term follow-up information (46). Although difficulties in following donors for either research or clinical surveillance and care have been discussed in many forums (14,24), such information is critical for understanding—and potentially intervening upon—the risks and potential sequelae of living liver donation. These activities will help to ensure that donor safety continues to come first.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Living liver donors are scheduled for routine follow-up after liver donation to ensure donor safety, and our data included routine checkup visits in living liver donors. As most institutions have a follow-up visit protocol similar to the clinical protocols of the Adult-to-Adult Living Donor Liver Transplantation Cohort Study, 21 4–6 scheduled postdonation routine checkup visits are included in the outpatient department visits during the first year. Therefore, the number of outpatient department visits in donors unrelated to liver donation may be considered similar to the second year and the years thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of kidney donors by Schold et al reported that women are more compliant with postdonation follow-up as are those who are older, married, and more educated which could translate to a higher survey response rate 22 ; white race and older age have also been found to be correlated with closer follow-up in the liver donor population. 23 Still, despite a higher prevalence of end-stage renal disease, minorities are persistently underrepresented as donors and living donor recipients—as are lower income individuals. A recent consensus conference 24 suggested areas for intervention to address the multifactorial roots of this disparity; among these are removing financial disincentives (discussed earlier) and increasing collaborative research on ways to break down the barriers to transplant or donation.…”
Section: Discussionmentioning
confidence: 99%